2019
DOI: 10.2166/wst.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale comparison of N2O emissions from SBR N/DN operation versus one-stage deammonification MBBR treating reject water – and optimization with pH set-point

Abstract: To be able to fulfill the Paris agreement regarding anthropogenic greenhouse gases, all potential emissions must be mitigated. Wastewater treatment plants should aim to eliminate emissions of the most potent greenhouse gas, nitrous oxide (N2O). In this study, these emissions were measured at a full-scale reject water treatment tank during two different operation modes: nitrification/denitrification (N/DN) operating as a sequencing batch reactor (SBR), and deammonification (nitritation/anammox) as a moving bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The N 2 O emission was divided by half (2-4% of N-load) when the granular SBR was operated under a new continuous aeration strategy. Similar observation was made by [16] comparing N 2 O emission of a full-scale sidestream SBR operated in nitrification/denitrification (N/DN) mode at Slottshagen WWTP in Sweden to that of a deammonification MBBR unit replacing the existing SBR for reject water treatment. While the N 2 O emission of the N/DN SBR was averaging 10% of incoming N-load, it was reduced to an average of 0.1-0.7% of incoming N-load for the deammonification MBBR operated under continuous feed and continuous aeration.…”
Section: Lessons Learned With Operation Control Strategysupporting
confidence: 63%
See 1 more Smart Citation
“…The N 2 O emission was divided by half (2-4% of N-load) when the granular SBR was operated under a new continuous aeration strategy. Similar observation was made by [16] comparing N 2 O emission of a full-scale sidestream SBR operated in nitrification/denitrification (N/DN) mode at Slottshagen WWTP in Sweden to that of a deammonification MBBR unit replacing the existing SBR for reject water treatment. While the N 2 O emission of the N/DN SBR was averaging 10% of incoming N-load, it was reduced to an average of 0.1-0.7% of incoming N-load for the deammonification MBBR operated under continuous feed and continuous aeration.…”
Section: Lessons Learned With Operation Control Strategysupporting
confidence: 63%
“…Nitrous oxide (N 2 O) emissions from sidestream deammonification processes have been often linked to specific operation control strategies employed by the different technologies such as feeding regime (continuous vs. batch), aeration control (continuous vs. intermittent), and substrate concentration gradient in the reactor [15,16]. Ref.…”
Section: Lessons Learned With Operation Control Strategymentioning
confidence: 99%
“…Chemical addition in the SBR could further lead to elevated carbon dioxide emissions from the bacterial reactions [8]. In a comparison between deammonification technologies and conventional nitrification/denitrification, it was found that the first emitted less nitrous oxide [50,51]. However, past studies also highlighted that the nitrous oxide emissions of deammonification can exceed the nitrification/denitrification when leaving the partial nitritation step uncontrolled with nitrite concentrations >20 mg N L À1 [52,53].…”
Section: Ammonia Recovery and Climate Change Mitigationmentioning
confidence: 99%
“…However, Blum et al 12 suggested that pH may regulate the rates between N 2 O production and consumption. Indeed, Kanders et al 50 showed that more N 2 O could be reduced via complete denitrification at higher pH (7.5−7.6 vs 6.6−7.1). However, in the present study, such influence was avoided by controlling a narrow pH range (7.5−7.9).…”
Section: Identification Of the Microbial Communitymentioning
confidence: 99%